Salt Stress and its Implications in Vegetable Crops with Special Reference to the Cucurbitaceae Family - Firdes Ulas; Hama Ameen, Hawkar Hama Hadi Hama Ameen; Abdullah Ulas (Annals of Arid Zone, 2024)
Salt stress is a significant abiotic factor that constrains agricultural productivity by impairing plant growth, particularly in arid and semi-arid regions. Vegetables, ranging from sensitive to moderately tolerant to salinity, experience adverse effects such as disruptions in seed germination, growth, flowering, and fruit development. Salinity hampers water uptake from the soil, as higher salt concentrations in the root zone increase the energy required by plants to absorb water. Sodium salts, in particular, interfere with the uptake of essential nutrients like nitrogen, phosphorus, and potassium, leading to nutritional imbalances. Furthermore, salinity induces oxidative and osmotic stress, ion toxicity, and hormonal disturbances, while also heightening plants‘ susceptibility to diseases. Crops in the Cucurbitaceae family, such as Cucumis sativus (cucumber) and Citrullus lanatus (watermelon), are known to exhibit diverse physiological and biochemical strategies to cope with salinity, including efficient ion transport regulation, osmolyte production, and antioxidant activity. Crops in the Cucurbitaceae family, such as Cucumis sativus (cucumber) and Citrullus lanatus (watermelon), exhibit diverse physiological strategies to cope with salinity. These traits are critical due to their economic significance in global agriculture. Understanding these mechanisms is crucial due to the economic significance of this family in global agriculture. This review examines the effects of salt stress on plant growth and development, explores tolerance mechanisms, and highlights the potential of crops from the Cucurbitaceae family to contribute to sustainable agricultural practices.